Transversal competencies among Peruvian dental students in times of the COVID-19 pandemic - Dora N. Gómez-Meza; Víctor F. Lamas-Lara; Manuel A. Mattos-Vela; Teresa A. Evaristo-Chiyong; Luis A. Cuadrao-Zavaleta; Maria Eugenia Guerrero (Humanities & Social Sciences Communications)
Abstract Transversal competencies are not related to any specific degree program but are crucial with respect to university students’ academic and professional training and entry into the labor force. Therefore, this study aimed to identify the transversal competencies (including instrumental, interpersonal, and systemic competencies) exhibited by Peruvian dental students in times of the COVID-19 pandemic as well as the relationships between these competencies and various sociodemographic characteristics. A cross-sectional study second to 6th-year students in a Peruvian dental school was performed. A validated paper and pencil questionnaire that collected information concerning transversal competencies was used in this research. This questionnaire contained three sections; the first section solicited informed consent, the second section focused on the sociodemographic characteristics of participants (6 items) and the third section pertained to transversal competencies (185 items). The survey was conducted between May and August 2022. Descriptive statistics were calculated with respect to each of the competencies investigated in this research. The Friedman, Dunn‒Bonferroni post-hoc, Mann‒Whitney U, and Kruskal‒Wallis tests were used to compare the variables included in this study. The three categories of competencies exhibited similar median values (3), while four subcompetencies exhibited lower median values. Furthermore, interpersonal competencies exhibited significantly lower values (p = 0.003) than did instrumental or systemic competencies. No statistically significant relationships were observed between each group of transversal competencies and the corresponding sociodemographic variables.